A Generalization of Prešić Type Mappings in 0-Complete Ordered Partial Metric Spaces. (18th September 2013) - Shukla, Satish; Radenović, Stojan
Abstract : The purpose of this paper is to prove some coincidence and common fixed point results for mappings satisfying Prešić type contraction condition in 0-complete ordered partial metric spaces. The results proved in this paper generalize and extend the results of Prešić and Matthews in 0-complete ordered partial metric spaces. Some examples are included which show that the generalization is proper.